Ecological and Ergonomic Aspects of Operating Hybrid Sunflower Cultivation Technologies - M. A. Kerimov; V. V. Vetushko (Сельскохозяйственные машины и технологии)
The technology for cultivating hybrid sunflower seeds is formalized as a biotechnical dynamic system structured around the «operator–machine–environment» triad. The efficiency of this system depends on multiple factors, primarily the qualification level of machine operators, the technical advancement of the machinery, and the conditions of both the production and external environments. (Research purpose) To enhance the efficiency of hybrid sunflower seed production technologies by developing and validating safe scientific and technical solutions. (Materials and methods) The system is characterized as probabilistic, with its state described by a mathematical model. The model’s input variables represent factors exerting positive, neutral, or negative impacts on the system. It is established that achieving optimal system performance requires the rational distribution and effective coordination of energy, material, and information flows across its subsystems. (Results and discussion) The study demonstrates that the research objective is achieved through two core systems engineering tasks: analysis, which involves identifying key parameters of the biotechnical system and environmental variables that exhibit probabilistic-statistical variability; and synthesis, which involves justifying an optimal control scheme for system operation. (Conclusions) The technological reliability of the biotechnical system, as a qualitative metric, reflects its capacity to perform designated functions while accounting for technical and economic indicators, ecological and ergonomic requirements, and time-related factors. Ergonomic requirements related to system design and parameter selection must take into consideration injury-inducing factors that affect the safety of hybrid sunflower seed production technologies. The convergence of pre-injury conditions and hazardous operator actions in time and space leads to injury, the occurrence of which can be mathematically modeled as a function. A comprehensive indicator – the injury risk criterion – is proposed and modeled as a function of harmful factors, including workplace dust concentration, ambient temperature, and the technical condition of the machine-tractor unit. A predictive model has been developed to estimate the number of potential injuries, and corresponding preventive measures have been substantiated. The agrotechnological application of the proposed model enables a 12-15% reduction in injury rates and facilitates the transition to safer cultivation technologies for hybrid sunflower seed production.